Determinan Internet Financial Reporting pada Perusahaan Manufaktur di Bursa Efek Indonesia - Wike Januriati; Salma Taqwa (Universitas Negeri Padang, 2023)
The use of the internet in the era of revolution 4.0 currently affects the traditional form of information presentation for companies. Technological developments, especially the internet, create opportunities to expand information dissemination through company websites in the form of up-to-date information in order to reduce information asymmetry in a company. This research aims to provide transparency and accountability to company stakeholders, including investors, employees, auditors and customers. One of the impacts of the internet for accountants is the emergence of IFR or online-based financial information providers. Internet Financial Reporting causes financial reporting to be easily accessible to anyone and can be traced for accuracy for investors. Thus, it is necessary to know the determining factors that encourage why companies need to implement IFR as a medium of communication with investors. This study used a sample of 85 manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021. The method used in this research is regression analysis, simple regression coefficient test (t test), and simultaneous regression test (F test) to find out what factors affect IFR. The variables used in this study are company size, profitability, liquidity, leverage, audit committee and audit quality. The results showed the variables that had a significant effect on IFR were company size and leverage of 0.000 and 0.031, while the variables of profitability, liquidity, audit committee and audit quality had no significant effect on internet financial reporting.